2015
DOI: 10.1007/s12250-015-3620-5
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus VP7 epitope chimeric proteins elicit cross-immunoreactivity in guinea pigs

Abstract: VP7 of group A rotavirus (RVA) contains major neutralizing epitopes. Using the antigenic protein VP6 as the vector, chimeric proteins carrying foreign epitopes have been shown to possess good immunoreactivity and immunogenicity. In the present study, using modified VP6 as the vector, three chimeric proteins carrying epitopes derived from VP7 of RVA were constructed. The results showed that the chimeric proteins reacted with anti-VP6 and with SA11 and Wa virus strains. Antibodies from guinea pigs inoculated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…14 Considerable efforts have been made toward development of subunit RV vaccine candidates (e.g., soluble antigens, virus-like particles) that are being evaluated in preclinical and early clinical studies. [15][16][17][18][19] One such candidate (referred to nonreplicating rotavirus [NRRV]) containing a trivalent mixture of recombinant truncated VP8* fusion proteins is in phase 1/2 clinical trials. Previously, one of the 3 antigens (P2-VP8-P [8]) was shown to be safe in healthy adults as well as to be well tolerated and immunogenic in infants and toddlers thus establishing the proof of concept.…”
Section: Introductionmentioning
confidence: 99%
“…14 Considerable efforts have been made toward development of subunit RV vaccine candidates (e.g., soluble antigens, virus-like particles) that are being evaluated in preclinical and early clinical studies. [15][16][17][18][19] One such candidate (referred to nonreplicating rotavirus [NRRV]) containing a trivalent mixture of recombinant truncated VP8* fusion proteins is in phase 1/2 clinical trials. Previously, one of the 3 antigens (P2-VP8-P [8]) was shown to be safe in healthy adults as well as to be well tolerated and immunogenic in infants and toddlers thus establishing the proof of concept.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging virus strains have been associated with mutations that render vaccines and other therapies, such as monoclonal antibodies, less effective as seen with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (Starr et al 2021). Previous studies have shown that the VP5* and VP8* outer capsid proteins play a significant role in inducing neutralising antibodies against rotaviruses (Ludert et al 2002; Park et al 2021; Ruggeri and Greenberg 1991; Zhao et al 2015). The VP5* protein of the Malawian G3P[8] strains were 100% conserved when compared to that of Rotarix vaccine, consistent with previous studies that have reported that the VP5* is a highly conserved protein (Rasebotsa et al 2020; Mwangi et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they are utilized frequently as candidates for genetically engineered RV vaccines [ 36 ]. Glycoprotein VP7 is a structurally neutralizing antigen of RVs that can elicit the production of immunoglobulin (Ig)G antibodies, which are associated with protection afforded by the immune system [ 37 ].…”
Section: Introductionmentioning
confidence: 99%